Estudos Comparativos de Fluxos Turbulentos e Erros Associados a sua Estimativa Acima da Floresta em Várias Regiões da Amazônia - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2007)
The forest-atmosphere turbulent exchange in different Amazon regions is investigated through studies of turbulent fluxes and the accuracy associated with their statistical calculation. This provides important subsidies for better understanding the structure of turbulence in the surface boundary layer, the energy balance, and the carbon cycle in the Amazon. In addition, the estimation of errors associated with the flux calculation uses the statistical parameter "correlation coefficient" (r), which helps to understand how the fluxes of the scalars, water vapor and CO2, are being generated between the forest and the atmosphere, during different periods of the day. The data used resulted from collections provided by the LBA, MILÊNIO-LBA and PRONEX-SECTAM projects, and are from the meteorological towers installed in the Caxiuanã Forest and in Rondônia (Forest of Rebio Jaru and Pasture) and were treated according to the methodologies proposed in the literature. For the Caxiuanã National Forest, the calculation of turbulent fluxes of C0t shows that the dryland forest in the region covered by the tower, on average, behaves as a carbon sink. It was determined that the accuracy associated with the calculation of fluxes varies between times of day and between the dry and wet seasons, with the morning and late afternoon hours showing the lowest accuracy. In the dry season, the error associated with flow was much higher in the early evening, around 7:30 pm, probably because strong gusts of wind occur at this time. Four patterns of CO2 and water vapor exchange between the forest and the atmosphere were also identified, based on the correlation coefficients between the concentration of these variables. For the Rondônia forest data, it is not possible to calculate the error associated with the flux at many times, due to strong non-stationarity conditions at the site. For the pasture, in Rondônia, the calculation of the estimate of the error associated with the flux also showed that the accuracy varies according to the time of day and the season, with the greatest inaccuracies being registered in the early morning and late afternoon periods. Thus we conclude that the Amazon forest regions studied present a diversified behavior in relation to the variability of the estimate of the error associated with the flux, both in relation to the time of day and in relation to the dry and wet seasons. Keywords: CO2 fluxes, variability, flux accuracy.
Comparative Studies of Turbulent Fluxes and Errors Associated with their Estimation Above the Forest in Several Regions of the Amazon
Keywords: Fluxos de CO2; Variabilidade; Precisão dos fluxos; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS